Risk Factors for Musculoskeletal Complaints in Nurses in Hospitals - Annisa Dipinta Hening Cahyaningratri; Indri Hapsari Susilowati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Musculoskeletal complaints are a common occupational health problem experienced by nurses in hospital settings, primarily resulting from patient‑handling activities such as lifting, transferring, and maintaining static or awkward postures for prolonged periods. These conditions have been reported with a very high prevalence and may lead to chronic pain, disability, and increased work absenteeism. The aim of this study was to analyze and identify the risk factors contributing to musculoskeletal complaints among hospital nurses. This study employed a systematic review design by searching the electronic databases ScienceDirect and PubMed using the keywords “risk factors”, “musculoskeletal complaints”, and “hospital nurses”. The inclusion criteria consisted of English‑language articles published between 2020 and 2025, free‑access, and full‑text availability. The study selection process followed the PRISMA protocol, resulting in 15 eligible articles. The review identified 18 risk factors associated with musculoskeletal complaints among hospital nurses: sex, BMI, age, marital status, education level, smoking habits, exercise habits, length of employment, lack of assistance and non‑use of assistive devices, working posture, work unit, work shift, employment status, workload, lack of training, job stress, low social support, and fatigue. The most frequently reported musculoskeletal complaints were located in the lower back, neck, and shoulders. These findings highlight the need for preventive measures such as ergonomics‑related training, stretching exercises, workload regulation, adequate rest periods, and the promotion of healthy lifestyle behaviors.Keywords: risk factors; musculoskeletal complaints; hospital nurses